Massbuild : culture "gets it done" - Urban, Angela; Viedge, Conrad (London : SAGE Publications Ltd, 2017)
In February 2015, Llewellyn Walters, CEO of Massbuild, the building products division of Massmart, a warehouse retail organisation, was perplexed by the results of the 2014 employee engagement survey. The survey showed that employee engagement had continued to decline for a third year. Walters reflected on his decision in 2009 to work on the adage "culture will eat strategy for breakfast" and initiate a culture change process as a means of ensuring that Massbuild achieved its strategic objectives. The decision to go the culture route had not only led to better results, but also facilitated decisions regarding the divisions brands and resulted in renewed customer focus. He wondered what more the organisation could do to reinforce its culture.
Originally published in Urban, A., & Viedge, C. (2015). Massbuild: Culture "Gets it done". WBS-2015-10. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Massbuild; Corporate culture; Organizational behavior; Building materials